Isolation and Identification of Toxin-Producing Fungi Associated with Some Potato Chips and Inhibition of Their Growth Using Plant Extracts - Ali, Hadeel Amoori Abd (American Journal of Biomedicine and Pharmacy, 2026)
This study involved the isolation and identification of fungi contaminating various types of potato and corn chips. 91 fungal samples were isolated, belonging to multiple genera, with a clear dominance of the genus Aspergillus, along with species such as A. niger, A. flavus, A. terreus, A. oryzae, and A. parasiticus, as well as Penicillium and other species such as Alternaria spp. and yeasts. The results confirmed that all isolates produced aflatoxins. Evaluations were conducted to test the effectiveness of alcoholic plant extracts from onion, clove, cinnamon, and rosemary in inhibiting the growth of these fungi. The results showed a variation in the degree of inhibition, depending on the fungal species and extract concentration. The variation in fungal response is attributed to the diversity of cell wall composition and fungal metabolic pathways, as these characteristics influence the ability of fungi to resist or be affected by active plant compounds. The study indicated the vital role of natural chemical compounds in inhibiting fungal growth through mechanisms such as disruption of cell membranes, inhibition of vital enzymes, and exposure to oxidative stress. These findings highlight the potential of using plant extracts as natural flavorings for gypsum chips or as safe and effective antifungals as alternatives to chemical pesticides. Their application is important as part of food safety strategies and to reduce food contamination with mycotoxins.